Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.2 - The Product and Quotient Rules - 3.2 Exercises - Page 188: 7



Work Step by Step

$g(x)=\dfrac{1+2x}{3-4x}$ Differentiate using the quotient rule $g'(x)=\dfrac{(3-4x)(1+2x)'-(1+2x)(3-4x)'}{(3-4x)^{2}}=\dfrac{(3-4x)(2)-(1+2x)(-4)}{(3-4x)^{2}}=...$ Evaluate the products in the numerator $...=\dfrac{6-8x+4+8x}{(3-4x)^{2}}=\dfrac{10}{(3-4x)^{2}}$ $y'=\dfrac{10}{(3-4x)^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.